Identifikasi Tantangan dan Solusi dalam Sistem Pembayaran Utang Usaha pada PT Intidaya Dinamika Sejati - Cristina H Siboro; Siti Sundari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research discusses the accounts payable payment system at PT Intidaya Dinamika Sejati by identifying the challenges faced and the strategic solutions that can be implemented to overcome these challenges, in order to improve the effectiveness of the company's debt management to suppliers. The challenges identified that caused obstacles in accounts payable management include delays in the invoicing verification process and a lack of coordination between the purchasing and finance departments. The approach used in this research is descriptive qualitative, with data collection techniques through observation and document studies. The results of the analysis show that internal factors, such as irregular administration and lack of internal controls, are the main causes of payment delays. The analysis results show that internal factors, such as the irregularity of administration and lack of internal control, are the main causes of payment delays. As a solution, the company is refining standard operating procedures (SOP), strengthening the information technology system by using an ERP service system, and enhancing the integration of the company's internal controls.